Effect of spike on steady and unsteady flow over a blunt body at supersonic speed. (November 2016) - Sahoo, D.; Das, S.; Kumar, P.; Prasad, J.K.
Abstract: Experimental and computational studies have been made to obtain the effect of spike shape and length on the flow over a blunt body at supersonic Mach number of 2at zero angles of attack. The spike used had a sharp tip, spherically blunt tip, and a flat aerospike tip. It is observed that use of a sharp spike leads to the reduction in drag by about 30%, whereas blunt or aerospike having the same length leads to about 45% reduction. Increasing the length of sharp spike reduces the drag. In general, the agreement between the computed and experimental result is found to be good. Flow unsteadiness has been captured through experiment and computation. An increase in unsteadiness is observed to be of the order of 20 dB due to the adoption of a spike, and the influence is mainly in the region close to spike and the main body. It has been observed that with an increase in spike length the pressure fluctuations increase and with the change in shape to blunt and aerospike the fluctuations decrease. Highlights: Effect of spike shape and length on blunt body aerodynamics. Flow unsteadiness captured on spiked blunt body at M =2 through experiments and computations. Increase in sharp spike length increases pressure fluctuations. Change of spike shape from sharp to blunt and aerospike decreases fluctuations.